2011
DOI: 10.1105/tpc.111.083329
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Regulatory Interactions from Genome Sequences Using a Biophysical Model for theArabidopsisLEAFY Transcription Factor  

Abstract: Despite great advances in sequencing technologies, generating functional information for nonmodel organisms remains a challenge. One solution lies in an improved ability to predict genetic circuits based on primary DNA sequence in combination with detailed knowledge of regulatory proteins that have been characterized in model species. Here, we focus on the LEAFY (LFY) transcription factor, a conserved master regulator of floral development. Starting with biochemical and structural information, we built a bioph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
217
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(239 citation statements)
references
References 57 publications
7
217
2
1
Order By: Relevance
“…The presence or absence of LEAFY binding sites identified by this approach appears to be helpful in predicting to what extent a C-clade gene acts as a true C-function gene. The PMADS3 second intron has already been shown to harbor LEAFY binding sites (Moyroud et al, 2011), in line with its role as C-function gene. We resequenced the PMADS3 second intron and newly sequenced the second intron of FBP6 and could identify putative LEAFY binding sites in both genes (Figures 1B and 1C), which, in the case of PMADS3, corresponds to the initial analysis (Moyroud et al, 2011).…”
Section: Quantitative Rt-pcr Shows Differential Expression Of the Ag mentioning
confidence: 88%
See 2 more Smart Citations
“…The presence or absence of LEAFY binding sites identified by this approach appears to be helpful in predicting to what extent a C-clade gene acts as a true C-function gene. The PMADS3 second intron has already been shown to harbor LEAFY binding sites (Moyroud et al, 2011), in line with its role as C-function gene. We resequenced the PMADS3 second intron and newly sequenced the second intron of FBP6 and could identify putative LEAFY binding sites in both genes (Figures 1B and 1C), which, in the case of PMADS3, corresponds to the initial analysis (Moyroud et al, 2011).…”
Section: Quantitative Rt-pcr Shows Differential Expression Of the Ag mentioning
confidence: 88%
“…The PMADS3 second intron has already been shown to harbor LEAFY binding sites (Moyroud et al, 2011), in line with its role as C-function gene. We resequenced the PMADS3 second intron and newly sequenced the second intron of FBP6 and could identify putative LEAFY binding sites in both genes (Figures 1B and 1C), which, in the case of PMADS3, corresponds to the initial analysis (Moyroud et al, 2011). In addition, we identified conserved CCAAT-boxes ( Figure 1D), which are a hallmark of AG genes playing a role in early flower development and are required (U) and (X) Scanning electron micrographs of the stigmatic surface of wild-type (U) and fbp6-1 (X) flowers.…”
Section: Quantitative Rt-pcr Shows Differential Expression Of the Ag mentioning
confidence: 88%
See 1 more Smart Citation
“…In addition to the described binding by BZR1 , BRs might also target PIF5 through direct binding by BES1 . Intriguingly, several transcription factors involved in the regulation of flowering (AP1, SVP, LFY, AG, and SEP3) have also been identified to bind PIFs (Kaufmann et al, 2009(Kaufmann et al, , 2010Moyroud et al, 2011;Tao et al, 2012;Gregis et al, 2013;ÓMaoiléidigh et al, 2013), suggesting a direct link to the reported flowering phenotype of pif mutants (Brock et al, 2010;Nozue et al, 2011;Kumar et al, 2012). Finally, binding by REV and AGL15 (Zheng et al, 2009;Brandt et al, 2012) suggests that some of the PIFs might be involved in leaf patterning or embryogenesis, a possibility that needs to be explored.…”
Section: Transcriptional Regulation Of the Pifsmentioning
confidence: 99%
“…As a control, we compared these data with the binding sites of LEAFY (LFY) (Moyroud et al, 2011), a transcription factor not known to be required for this morphogenetic response. We found that many shade upregulated genes were bound by PIF5, PIF4, ARF6, and BZR1 (Figures 3A and 3B).…”
Section: Pif Transcription Factors Directly Regulate Many Early Shadementioning
confidence: 99%